Penguatan Literasi Digital melalui Peranan Media Sosial Bagi Generasi Muda - Sholahudin Al’Ayubi; Tri Novita Irawati (Universitas Islam Nahdlatul Ulama Jepara, 2022)
In the era of the industrial revolution 4.0, access to information can be received directly from anywhere and at any time through the use of the internet. From year to year the use of the internet is increasing, especially in the use of social media by most of the younger generation. Therefore it is necessary to strengthen the abilities and skills of the younger generation in digesting the information obtained. In this case digital literacy plays an important role in changing the analytical and critical mindset in receiving existing information. This service activity is in the form of counseling/providing material related to strengthening digital literacy through the role of social media online and offline. The method of this activity includes problem identification, planning, preparation, counseling/delivery of material and evaluation. The result of this activity is an increased understanding of digital literacy through the role of social media. Based on the activities that have been carried out, it has given a positive response to the younger generation in the form of a very good level of understanding, namely more than 50% of online and offline participants really understand the material presented.